TALKING STICK LEARNING MODEL APPLICATION TO IMPROVE STUDENT LEARNING RESULTS IN INDONESIAN LEARNING AT CLASS V SDN 9 SINDUE TOMBUSABORA - Lini Andriani; Sahrudin Barasandji; Ulinsa Ulinsa (Jurnal Dikdas, 2022)
The problem in this research is the low student learning outcomes of grade V SDN 9 Sindue tombusabora in Indonesian subjects. This study aims to prove that the application of the Talking Stick learning model can improve the learning outcomes of Grade V SDN 9 Sindue tombusabora students. The research subjects were 24 students. This type of research is classroom action research consisting of two cycles, each cycle consisting of, planning, implementing, observing, and reflecting. The results of the pre-action test showed the percentage of classical learning completeness was 8.33% and classical absorption was 54.42%. The results of this study indicate an increase in student learning outcomes from cycle I to cycle II. The results of the study in the first cycle showed the percentage of classical absorption (DSK) of students was 66.92% and the percentage of mastery learning (KBK) was 45.83%. While in the second cycle the percentage of students 'classical absorption (DSK) was 77.08%, and the percentage of students' classical learning completeness (KBK) was 79.16%. Teacher activity in the first cycle reached 80.76% with good criteria, in the second cycle an increase of 88.46% with a very good category. Based on the results of the study showed that the learning outcomes of the Indonesian language field of study could be improved through the application of the Talking Stick learning model for fifth grade students of SDN 9 Tombusabora.